ANALYSIS OF PHYSICAL EDUCATION INSTRUCTION USING ASYNCHRONOUS METHOD ON A DISTANCE LEARNING SYSTEM - Leli Rahman; Taufik Rihatno; Fatah Nurdin (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to find out how the level of learning activity using the method asynchronous in distance learning. The research method uses descriptive analysis method. The research population was students of SMAN 1 Cisarua in the 2020/2021 academic year with a total sample of 90 people, while the instrument used in this study was a learning activity questionnaire. The data analysis technique used relative frequency distribution and trend test. The results showed that the "Very Good" category obtained a percentage of 8%, in the "Good" category a percentage of 22% was obtained, in the "Enough" category a percentage was obtained 41%, in the "Less" category the percentage was 23%, while in the "Very Poor" category, a percentage of 6% is obtained. From the results of this study, it can be concluded that the level of physical education learning activities through the use of asynchronous media is in the sufficient category, although in terms of implementation it is still not optimal and there are several shortcomings, but the most important thing is that learning activities must continue to be carried out even in limited conditions